أخلاقيات العمل الطبي و ضوابطه و آداب الطبيب المطلوب في الشريعة الإسلامية: Ethics and Rules for Medical Practice and Requisite Etiquettes for Doctors in Islamic Law - Mariam Hafeez; Dr. Samina Bashir (Al-Amīr Research Journal for Islamic Studies, 2025)
The paper at hand attempts to explore the requisite ethical responsibilities and moral guidelines that shape the medical profession in Islamic law. It features the essential traits that a physician must embody to ensure their efficacy in both their professional and spiritual roles. In Islam, a doctor’s responsibility is not only to heal but also to maintain a strong moral compass, as the profession is considered one of the most revered due to its direct impact on human life and well-being. This includes the duty to be honest, transparent, and compassionate; especially while handling sensitive patient information and making crucial decisions. The article further emphasizes over the importance of physicians maintaining high standards of professionalism and ethics by persistently educating themselves to stay updated on advancements in medical science. With medical knowledge evolving rapidly, it is essential that doctors participate in lifelong learning to provide the best care possible for their patients. Additionally, the physician’s duty extends beyond medical knowledge and skill, requiring them to engage with patients respectfully, considering their psychological, social, and cultural contexts. Moreover, the article elaborates the significance of a physician’s duty to the community, emphasizing that their role goes beyond the individual patient. Physicians are encouraged to actively participate in public health initiatives, ensure the equitable distribution of healthcare and provide guidance in preventing and controlling disease outbreaks. The ethical obligation to avoid exploitation of patients or using their position for personal gain is also stressed, underlining the importance of integrity in maintaining trust within the profession. Finally, the article ties these professional and ethical expectations to broader Islamic principles, asserting that the doctor’s role is not just a medical profession but a form of service to humanity, aligned with divine teachings. By embodying these ethical guidelines, physicians are not only fulfilling their professional obligations but are also making a profound spiritual contribution, as their work directly aligns with the values of compassion, justice and caution accentuated in Islam. Keywords: Islamic Law, Medical Practice, Ethics, Physician, Health